Dynamics of Phytohormones in Persistent Versus Deciduous Calyx Development in Pear Revealed by Targeted Metabolomics - Mingyang Yu; Feng Han; Nana Zhou; Lanfei Wang; Yang Li; Weifan Fan; Tianzheng Zhang; Jianping Bao (Horticulturae, 2025)
To calyx persistence in Korla fragrant pear (Pyrus sinkiangensis) significantly impacts fruit marketability, with persistent calyx causing up to 40% reduction in premium-grade fruit yield. Investigating the hormonal mechanisms underlying calyx abscission and persistent in Korla Fragrant Pear, we performed comprehensive phytohormone profiling using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS; EXIONLC system coupled with SCIEX 6500 QTRAP+). Flowers from first-position (persistent-calyx) and fourth-position (deciduous-calyx) inflorescences were collected at six developmental stages (0–10 days after flowering). Fourteen endogenous hormones—ACC, ME-IAA, IPA, TZR, SA, IAA, ICA, IP, tZ, DHJA, ABA, JA-ile, cZ, and JA—were identified in the calyx during the flowering stage. The calyx abscission rate was significantly higher in the fourth position (79%) compared to the first position (32%). ACC and ABA are closely linked to abscission, with increased ACC at 0 DAF signaling early abscission and ABA accumulation accelerating late abscission at 8 DAF. Auxin exhibited spatiotemporal specificity, peaking in first-order flowers at 4–6 DAF, potentially inhibiting abscission by maintaining cell activity. Cytokinins generally decreased, while jasmonates significantly increased during the fourth-position anthesis stage 8–10 DAF, suggesting a role in stress-related senescence. By systematic analysis of the flowers at the first order (persistent calyx) and the fourth order (deciduous calyx) from 0 to 10 days after anthesis, we found three key stages of hormone regulation: early prediction stage (0–2 DAF), ACC accumulation at the fourth order was significantly higher than that at the first order at 0 days after anthesis, ACC accumulation at the early stage predicted abscission; During the middle maintenance stage (4–6 DAF), the accumulation of cytokinin decreased significantly, while the accumulation of IAA increased significantly in the first position (persistent calyx); Execution Phase (8–10 DAF), ABA reached its peak at 8 DAF, coinciding with the final separation time. JA played an important role in the late stage. Gibberellin was undetected, implying a weak association with calyx abscission. Venn diagram identified N6-(delta 2-Isopentenyl)-adenine (IP) in first-position flowers, which may influence calyx persistence or abscission. These findings elucidate hormone interactions in calyx abscission, offering a theoretical basis for optimizing exogenous hormone application to enhance fruit quality.